Structural Disparities in the Polish Economy: Regional Development - Janusz Wielki; Inessa Sytnik; Artem Stopochkin (Barometr Regionalny, 2019)
The purpose of this study is to identify structural imbalances in the regional development of the Polish economy on the basis of the level and specifics of regional development analysis. In order to achieve this goal, the data from the Polish Central Statistics Office describing the labor market, and the demographic and economic situation in Poland have been utilized. The analysis period is 2005–2016. The heterogeneity of regional development generates a number of economic, social and political issues, the solution of which requires the formation of a fundamentally new sustainable development policy concept. Such a concept is supposed to be based on an integrated approach that takes into account the specifics of development each individual region in the country.